Quasi-Static Properties of One-Dimensional Permalloy Nanostructures: A Comparative Analysis as a Function of Geometrical Parameters - Escrig-Murua, J (ASOC FISICA ARGENTINA, 2022)
The present study describes the magnetic properties of nanotubes and nanowires of Permalloy through micromagnetic simulations. These properties are evaluated as a function of the external diameters of such one-dimensional nanostructures when the magnetic field applied is parallel and perpendicular to the easy axis of the nanostructures. In addition, the diameter of the nanostructures was also varied in order to discuss the similarities and differences in the magnetic properties as a function of their length.